KEPASTIAN HUKUM BAGI KREDITOR KONKUREN DALAM PENYELESAIAN DAN PEMBERESAN BOEDEL KEPAILITAN - Ritonga, Francois Geny (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
In connection with the declaration of the Debtor in Bankruptcy with all the legal consequences, the debtor will lose his right to control and manage his assets which are included in the bankruptcy assets, so a Curator will be appointed to settle the bankruptcy assets. Arrangements carried out by the Curator to distribute bankruptcy assets (boedel) to creditors based on priority order where creditors with higher positions receive distribution first than other creditors with lower positions as regulated in the Undang-Undang Nomor 37 Tahun 2004 Tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang (“hereinafter referred to as the Bankruptcy and PKPU Law”) as referred to in the Elucidation of Article 2 paragraph (1). However, the implementation of legal principles and norms is difficult to apply in practice, resulting in injustice for concurrent creditors.